Advanced Ti3C2Tx MXene‐modified cement nanocomposites toward high efficiency electromagnetic functional materials for green buildings. Issue 1 (28th September 2022) - Wei, Fada; Liu, Qinghua; Liu, Heqiang; Wang, Guohong; Li, Minghang; Li, Mingxing; Liu, Xingmin
Abstract: The proliferation of electronic devices and wireless communication is leading to serious electromagnetic (EM) interference. In this work, Ti3 C2 /cement composites were developed as high efficiency EM functional materials by introducing exfoliated Ti3 C2 Tx MXene with cement for green buildings with EM shielding function. In the composites, few‐layered Ti3 C2 MXene were dispersed homogeneously throughout the cement matrix. The EM properties of the composites were studied as a function of the MXene content. With increasing MXene content, real and imaginary part of permittivity was significantly improved owing to the polarization and electrical conduction caused by the MXene phase. Composites with 15 wt.% MXene showed good EM absorbing properties with a maximum effective absorbing bandwidth of 2.67 GHz. Strong EM shielding can be achieved when MXene content increased to 25 wt.%. The EM shielding effectiveness of such composites was higher than 22.0 dB, and the dominating shielding mechanism was EM absorption. This work finds new materials for the development of advanced green buildings with EM shielding function.